The Effect of Human Resource Management Strategies on the Performance of the Organization A Field Study in the Syrian Companies for the Plastic Industries (Latakia University Journal - Economic and Legal Sciences Series, 2022)
This research was conducted to determine the effect of the human resource management strategies (human resource planning, recruitment and appointment, training and development, motivation, performance evaluation) on the performance of the organization, in a sample of Syrian companies for plastic industries. The researcher distributed (80) questionnaires to a sample of workers in the industrial companies under study and from different administrative levels (higher, middle, and lower). The number of questionnaires that were adopted in the statistical analysis was (71) questionnaires. The researcher analyzed the data using the statistical analysis program (SPSS 25).     At the end of this research, the researcher reached a number of conclusions, the most important of which is: There is a statistically significant effect of human resource management strategies (human resource planning, recruitment and appointment, training and development, motivation, performance evaluation) on the performance of the industrial companies under study. The researcher also made a number of recommendations, including: That the industrial companies under study continue to link their human resources planning with their ultimate goals, and give priority to investing in human capabilities and skills by adopting appropriate strategies that ensure the completion of various human resources management activities with the required efficiency, in addition to the necessity of selecting and appointing workers based on submitting an application for employment and knowing their capabilities In dealing with others, their ability to lead, knowing their intelligence levels, their motivation to work, and subjecting them to personal tests and interviews, and this is through the company's belief in placing the right man in the right place.